The effect of Ferula szowitsiana extract on chemical pain in male Wistar rats - Saghravanian, Seyed Javad; Fereidoni, Masoud; Asadollahi, Ali (Archives of Biological Sciences, 2018)
Investigations on the use of medicinal plants are appealing to researchers. In Iranian traditional medicine, Ferula szowitsiana is used as an analgesic. This study investigates the effect of the extract of aerial parts of Ferula szowitsiana on an experimental model of chemical pain induced by subplantar injection of formalin. The Ferula szowitsiana hydroalcoholic extract was prepared with ethanol, Tween 80 and saline at a ratio of 8:1:1 serving as a solvent. Wistar Rats in the weight range of 200-250 g were divided into 10 groups randomly (n=7) according to treatment applied as follows: control; solvent (intraperitoneal, i.p.); solvent (intrathecal, i.t.); extract (50, 100, 200, 400 mg/kg i.p.); extract (80 µg/10 µL i.t); naloxone (2 mg/kg i.p.); extract (400 mg/kg) and naloxone (i.p.). To study the chemical pain, subplantar administration of formalin was performed in all groups. The results showed that the extract could reduce chemical pain in the neurogenic and inflammatory phase dose dependently as compared to the control group. The magnitude of the response after intrathecal administration of a dose of 80 µg/10µL was comparable to that observed with 400 mg/kg of extract administered via the intraperitoneal route. The administration of naloxone as an opioid receptor antagonist reversed the analgesic effect of the extract completely. According to the results, it seems that at least a significant part of the analgesic effect of Ferula szowitsiana extract is exerted through its effect on the central nervous system, and the analgesic effect of the extract in acute and inflammatory chemical pain is due to its effect on the opioid system. https://doi.org/10.2298/ABS170326054S Received: March 26, 2017; Revised: May 19, 2017; Accepted: June 2, 2017; Published online: December 21, 2017 How to cite this article: Saghravanian SJ, Fereidoni M, Asadollahi A. The effect of Ferula szowitsiana extract on chemical pain in male wistar rats. Arch Biol Sci. 2018;70(2):365-9.